EFFECTS OF TECHNOLOGY IN SPEAKING INSTRUCTION ON ENGLISH LANGUAGE LEARNERS STUDYING CYBERSECURITY - Abulkasimova, Yulduzkhan Sunnatillayevna (INTERNATIONAL CONFERENCES, 2023)
This essay discusses the influence of technology on students learning to speak English through speaking lessons. This article showed that instruction on how to speak in using modern English technology like video conferencing, email correspondence, and social media interactivity, live emceeing, and onstage speaking events where students participate in genuine both in the classroom and at work. Additionally, research showed that these technologies in speech instruction develop trust, improve fluency and accuracy, reduce fear and trepidation, and boost confidence among students. The researcher apparently discovered that the technology utilized in speaking instruction can be connected with the communicative approach to education, enabling pupils to express themselves in a skillful and competent manner.